Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Berbantuan Game Quizlet untuk Meningkatkan Hasil Belajar Peserta Didik Mata Pelajaran Al-Qur’an Hadits Kelas VIII di MTs DDI Masamba Kabupaten Luwu Utara - Oktafiani, Fani; Raupu, Sumardin; Arifanti, Dwi Risky; Zahira; Marwiyah, St.; Mawardi (Indo-MathEdu Intellectuals Journal, 2026)
The main focus of this study is to evaluate student participation during the learning process, the implementation level, and the improvement of student learning achievement in the Al-Qur’an Hadith subject through the use of a cooperative learning approach of the Teams Games Tournament (TGT) type assisted by the Quizlet game in Grade VIII of MTs DDI Masamba. This study employed a Classroom Action Research (CAR) design involving 25 eighth-grade students of MTs DDI Masamba as research subjects. Data were collected through observations of teacher and student activities, as well as learning test results used to assess the improvement of students’ abilities. The findings revealed that the average level of student engagement in the first cycle was 79.16%, categorized as “fair,” and increased in the second cycle to 87.49%, categorized as “good.” The implementation of the Teams Games Tournament (TGT) model assisted by the Quizlet game as a cooperative learning strategy achieved an average of 82.68% in the first cycle (“good”) and improved to 91.34% in the second cycle (“very good”). Furthermore, in the pre-test results, 100% of students were in the “very poor” category. In the first cycle post-test, 82.6% of students achieved mastery with a “good” category, and in the second cycle post-test, 100% of students achieved mastery with a “very good” category.